Análisis, comparación y diseño optimizado para muros de Contención - Mendieta-Molina, Edwin Alberto (Instituto Tecnológico de Costa Rica, 2016)
Retaining walls are structural elements used to contain masses of soil, which are being analyzed in this document are mainly compound of two elements, the stem and the base plate. There are many types and designs of walls, 2 of the most common are the walls of reinforced concrete and reinforced masonry walls, multiple designs for this thesis for two types of walls will be made, achieving an optimized design 5 high wall, varying geometric design, which the same assumptions for reinforced concrete walls and masonry. Likewise, the design will be held for 2 soil types, solid ground (S1) and a fairly rigid floor (S3). Optimized designs are modeled using a structural analysis software to obtain the steel of each wall then be budgeted in order to know their value. With the structural design of the wall and the cost of construction, a comparative table where the engineer, have a point of reference for selecting a type of retaining wall made for his/her project. A short chapter to the presentation of new construction alternatives with less environmental impact and an environmental review of the construction of the walls will go.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2016.
Keywords: Muros; Contención; Cimentaciones; Mampostería; Costo